Strategi Adaptasi Masyarakat Pasca Bencana Alam - S. Kaseng, Ernawati (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This article describes strategies that communities can adopt in the aftermath of natural disasters. Literature study is a method used in research, to describe a series of activities related to secondary data collection techniques. By reading and recording and processing research materials which are then reviewed by the researcher. The data is analyzed through the stages of recording important and relevant parts related to research problems and then compiled for analysis and drawing conclusions. The research output of this article is that post-disaster community adaptation is an interaction process of various forms of individual, group or community adjustment to the physical and social environment to achieve community survival and development in various aspects of life. For example, people may adopt active strategies such as finding additional work, engaging in mutual aid, or relying on assistance from social institutions. On the other hand, there are also passive strategies such as reducing spending to meet daily needs or following certain religious traditions in the face of natural disasters, including economic, social and cultural adaptation. Factors that influence community adaptation strategies after natural disasters involve economic and social aspects. Awareness of the importance of improving environmental conditions, strong social interaction and emotional attachment to the living environment play a key role in the adaptation process.